Analisis Kontribusi Bea Balik Nama Kendaraan Bermotor Dan Pajak Kendaraan Bermotor Terhadap Pendapatan Asli Daerah Provinsi Sumatera Selatan Tahun 2016-2019 - Bella Artha Ningsih; Harsi Romli; Andini Utari Putri (Jurnal Bisnis, Manajemen, dan Ekonomi, 2021)
This study aims to analyze the contribution of motorized vehicle name transfer fees and motor vehicle taxes to the regional revenue of South Sumatra Province in 2016-2019. The data used in this study is the report on the realization of the transfer of motor vehicle name transfer, motor vehicle tax, and local revenue from South Sumatra Province in 2016-2019. This research method uses a quantitative approach using multiple linear regression as a measuring tool to test the hypothesis. The results showed that the variable of motorized vehicle name transfer fee, motor vehicle tax had a positive effect on the variable of local revenue in South Sumatra Province.